Medicinal plants as alternative to anthelmintics for livestock : An overview with particular reference to Indian subcontinent - PATHAK, K M L; CHHABRA, M B (The Indian Journal of Animal Sciences, 2014)
In livestock farming helminthiasis remains a major constraint to productivity, performance and profitability. Anthelmintics have been in use since long to combat the problem, but the emergence of anthelmintic resistance, particularly in gastrointestinal (g.i.) parasites has compelled a relook at alternative control strategies. The application of ethno-veterinary practices and plant derivatives as deworming agents is gaining popularity worldwide. The acceptability of this approach depends on the scientific validation of the plant products for their anthelmintic properties. Several controlled studies recently carried out in the Indian subcontinent, generated a large volume of data on in vitro, in vivo and clinical efficacies of plants and herbs singly and in combination. Most have used internationally accepted guidelines as parameters for evaluation of the candidate plants. The target helminths in these studies belonged to 3 major classes, but gastrointestinal (g.i.) nematodes, liver flukes of ruminants and intestinal worms of poultry were predominant. Active principles and mode of action were identified in majority of plants, which have proven anthelmintic potential. Lately, the use of forages containing condensed tannins, is finding favour in the management of g.i. nematodes in ruminants. A cross-section of recent studies, an overview of the current scenario, and the road ahead, are presented in this review.